Rapidly Growing Chondroid Syringoma of the External Auditory Canal: Report of a Rare Case. (15th September 2011) - Vasileiadis, Ioannis; Kapetanakis, Stylianos; Petousis, Aristotelis; Karakostas, Euthimios; Simantirakis, Christos
Abstract : Introduction . Chondroid syrinoma of the external auditory canal is an extremely rare benign neoplasm representing the cutaneous counterpart of pleomorphic adenoma of salivary glands. Less than 35 cases have been reported in the international literature. Case Presentation . We report a case of a 34-year-old male in whom a rapidly growing, well-circumscribed tumor arising from the external auditory canal was presented. Otoscopy revealed a smooth, nontender lesion covered by normal skin that almost obstructs the external auditory meatus. MRI was performed to define the extension of the lesion. It confirmed the presence of a 1 . 5 × 0 . 8 cm T2 high-signal intensity lesion in the superior and posterior wall of EAC without signs of bone erosion. The patient underwent complete resection of the tumor. The diagnosis was confirmed by histopathologic examination. Conclusion . Although chondroid syringoma is extremely rare, it should always be considered in the differential diagnosis of an aural polyp. Chondroid syringomas are usually asymptomatic, slow-growing, single benign tumors in subcutaneous or intradermal location. In our case, the new information is that this benign tumor could present also as a rapidly growing lesion, arising the suspicion for malignancy.